EARLY POST-OPERATIVE COMPLICATIONS AFTER THYROIDECTOMY FOR BEING GOITE: Complication after Thyroidectomy - Mahmood, Khalid; Javed, Mohammad Asghar; Khan, Imran; Gul, Nadia; Mushtaq, Hina (Pakistan Armed Forces Medical Journal, 2009)
Objective: To find frequency of early complications after thyroid surgery for benign thyroid conditions. Study design: Quasi-experimental study. Place and Duration of study: Combined Military Hospital (CMH) Lahore, from March 2005 to Sep 2007. Patients and Methods: Early complications after thyroid surgery for benign thyroid conditions were studied. One hundred patients with FNAC confirmed benign goiter or follicular growth admitted for elective thyroidectomies were included in the study. Data was collected in the pre-designed proforma and entered in SPSS-10 version. Descriptive statistics was used to calculate frequency of each complication in the early post-thyroidectomy period. Results: The frequency of complications after thyroidectomy was 27%. Out of them 8 patients (8%) developed subcutaneous haematoma, 5 patients (5%) wound infection, 4 patients (4%) tension haematoma, 4 patients (4%) hypocalcaemia, 3 patients (3%) respiratory obstruction and 3 patients (3%) developed recurrent laryngeal nerve paralysis. Conclusions: Surgery for benign thyroid enlargement but may be associated with significant numbers of post operative complications including wound haematoma, wound infection and hypocalcaemia.